Hubungan Obesitas Dengan Migrain di Poliklinik Saraf RSUD Dr. Moewardi Surakarta - Delia, Kharima Sari, dr. Listyo Asist Pujarini, M.Sc, Sp.S, dr. Dona Dewi Niriawati (2015)
Background: Obesity refers to an excessive accumulation of body fat which leads to health problems, including migraine. Obesity is associated with the metabolic syndrome, a pro-inflammatory, pro-thrombotic state that may contribute to headache development and progression. Stimulation of trigeminal nociceptor induced the release of pro inflammation substances especially calsitonin-gene related peptide (CGRP) and P substance. Those substances are found higher in migraine and obesity person. Neurogenic inflammation state was known has a big role on migraine pain. Objective: To evaluate the association between obesity and migraine in Neurologic Clinic of Dr. Moewardi General Hospital Surakarta Methods: This study design based on observational analytics with case control methods. 30 total samples with 15 case samples and 15 control samples were included based on purposive sampling technique. Data presented on table and then analyzed using Chi-Square test. Result: Result from 15 migraine samples, 12 samples were obese (80%), while 15 non migraineurs only 3 samples were obese (20%) (p 0,001, OR=16,000, 95% CI:[2,674-95,754]). Conclusion: There is association between obesity and migraine.